Automatic classification of personal conflict styles in conflict resolution - Carneiro, Davide Rua (2011)
Carneiro D., Gomes M., Novais P., Andrade F., Neves J. Automatic Classification of Personal Conflict Styles in Conflict Resolution. In Legal Knowledge and Information Systems - JURIX 2011: The Twenty-Fourth Annual Conference, Katie M. Atkinson (Ed), IOS Press - Frontiers in Artificial Intelligence and Applications, Vol. 235, ISBN 978-1-60750-980-6, pp 43-52, 2011.